Use of serum lactate levels to predict survival for patients with out-of-hospital cardiac arrest: A cohort study - Williams, Teresa; Martin, R.; Celenza, A.; Bremner, A.; Fatovich, D.; Krause, J.; Arena, S.; Finn, Judith (Wiley-Blackwell Publishing Asia, 2016)
Objectives: We examined the association of serum lactate levels and early lactate clearance with survival to hospital discharge for patients suffering an out-of-hospital cardiac arrest (OHCA). Methods: A retrospective cohort analysis was performed of patients with OHCA transported by ambulance to two adult tertiary hospitals in Perth, Western Australia. Exclusion criteria were traumatic cardiac arrest, return of spontaneous circulation prior to the arrival of the ambulance, age less than 18 years and no serum lactate levels recorded. Serum lactate levels recorded for up to 48h post-arrest were obtained from the hospital clinical information system, and lactate clearance over 48h was calculated. Descriptive and logistic regression analyses were conducted. Results: There were 518 patients with lactate values, of whom 126 (24.3%) survived to hospital discharge. Survivors and non-survivors had different mean initial lactate levels (mean±SD 6.9±4.7 and 12.2±5.5mmol/L, respectively; P<0.001). Lactate clearance was higher in survivors. Lactate levels for non-survivors did not decrease below 2mmol/L until at least 30h after the ambulance call. Conclusion: In OHCA patients who had serum lactate levels measured, both lower initial serum lactate and early lactate clearance in the first 48h following OHCA were associated with increased likelihood of survival. However, the use of lactate in isolation as a predictor of survival or neurological outcome is not recommended. Prospective studies that minimise selection bias are required to determine the clinical utility of serum lactate levels in OHCA patients. © 2016 Australasian College for Emergency Medicine and Australasian Society for Emergency Medicine.